Analisis Penggunaan Media Interaktif Berbasis Canva pada Mata Pelajaran IPAS Materi Ekosistem di MIS Al-Azhar Ajung Jember - Manasikana, Arina; Dwi Anggi Ainun Marsiyah; Iftitahur Rizqi Amaliyah; Muhammad Suwignyo Prayogo (Jurnal Ilmiah Literasi Indonesia, 2025)
This study aims to analyze the use of Canva-based interactive media in teaching Natural and Social Sciences (IPAS) ecosystem material at MIS Al-Azhar Ajung, as well as to determine the responses of teachers and students to its application. Using a qualitative descriptive approach, data were collected through observation, interviews, questionnaires, and documentation with one IPAS teacher and twenty fifth-grade students as subjects. The results showed that the use of Canva increased student engagement, motivation, and conceptual understanding of ecosystem material. Teachers felt that Canva's visual and animation features helped them convey abstract concepts such as food chains and relationships between living things. Students responded positively, showing high levels of interest and participation during the learning process. Canva also encouraged student collaboration through group digital projects and developed critical and creative thinking skills. Despite technical constraints such as device limitations and preparation time, Canva proved to be effective in creating active, interactive, and meaningful learning.